INTEGRASI NILAI KEARIFAN LOKAL DALAM MATA PELAJARAN MATEMATIKA KELAS III - Shinta Dewi; Sri Handayani; Ema Butsi Prihastari (Widya Wacana: Jurnal Ilmiah, 2022)
The purpose of this study is 1) Find out the results of the analysis of the integration of local wisdom values ​​in Mathematics for grade III at SDN Parangjoro 01 Academic Year 2021/2022. 2) Knowing the factors that support the implementation of the integration of local wisdom values ​​in Grade III Mathematics at SDN Parangjoro 01 Academic Year 2021/2022. 3) Knowing the factors that hinder the implementation of the integration of local wisdom values ​​in Mathematics for grade III at SDN Parangjoro 01 Academic Year 2021/2022. Interview data collection techniques, documentation and literature study. The results of this study are the integration of local wisdom values ​​in Mathematics, namely the assimilation or integration between local wisdom values ​​and Mathematics subject matter taught in class III. Keywords: Mathematics,Local Wisdom, Third Grade